Layer-by-layer fabrication of restricted access media-molecularly imprinted magnetic microspheres for magnetic dispersion microextraction of bisphenol A from milk samples. (2nd March 2015) - Lv, Yun-Kai; He, Yan-Dong; Xiong, Xue; Wang, Jin-Zhi; Wang, Hai-Yan; Han, Ya-Meng
<x xml:space="preserve">Abstract</x> A novel hydrophilic BPA-imprinted magnetic microsphere was prepared with specific molecular recognition (2.54), water compatibility and exclusion biomacromolecules.